Risk Factors for Pre-Eclampsia in Pregnant Women at RSUD dr. ABDUL Rivai Berau - Dewi, Suci Christina; Hadiningsih, Eka Frenty; Masyita, Gita; Risnawati, Risnawati (Journal of Midwifery and Nursing, 2024)
Based on medical record data from RSUD dr. Abdul Rivai Berau is known to have 395 cases of pre-eclampsia pregnant women in January-October 2023. Risk factors that play an important role in the occurrence of pre-eclampsia: To determine risk factors for pre-eclampsia in pregnant women was age, parity, history contraceptives and multiple pregnancies. Type of research carried out was quantitative research with an analytical survey research design and a retrospective design. The population is all data pre-eclampsia cases in pregnant women January to October 2023 totaling 395 people, the Slovin formula sample of 199 people was obtained. The sampling technique uses simple random sampling. Data analysis using ch square. Age not at risk 57.8%, multigravida parity 55.3%, no history of using hormonal contraceptives 54.3%, no multiple pregnancies 51.8% and classification of mild pre-eclampsia 54.3%. There is a relationship between age and incidence of pre-eclampsia (p value = 0.009). There is a relationship between parity and incidence of pre-eclampsia (p value = 0.026). There is a relationship between a history of hormonal contraceptive use and the incidence of pre-eclampsia (p value = 0.011). There is a relationship between multiple pregnancies and incidence of pre-eclampsia (p value = 0.014). Age, parity, history of using hormonal contraceptives and multiple pregnancies as risk factors for pre-eclampsia in pregnant women. It is hoped RSUD dr. Abdul Rivai Berau provides health counseling or education to pregnant women preventing pre-eclampsia by providing material related to risk factors for pre-eclampsia in pregnant women along with their treatment and prevention